2009
DOI: 10.1504/ijscc.2009.024558
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive control of a parallel robot via backstepping technique

Abstract: The adaptive backstepping technique is applied to set point control of a planar parallel robot. The dynamic model of the robot is characterised by a set of differential algebraic equations. The model is reduced into a set of Ordinary Differential Equations (ODEs). A model-based adaptive backstepping controller is designed. The proposed controller is tested by experiments. Comparison among the adaptive backstepping controller, backstepping controller, adaptive PD controller and PD controller is made based on ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Zhang and Wei [21] indicated that adaptive control is generally divided into three categories, model reference control, selftuning control and gain schedule control, and presented a review and discussion on the model reference control of parallel manipulator. Wang et al [22] proposed an adaptive back-stepping technique for point control of a planar parallel robot, and experimental results showed that the adaptive back-stepping controller outperforms all the other controllers (mentioned in the paper, i.e., back-stepping controller, adaptive controller, adaptive PD controller, and PD controller) in terms of steady-state errors. Honegger et al [23] proposed a nonlinear adaptive control algorithm and conducted parameters identification of a 6-PSS parallel manipulator employed as a high-speed milling machine.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang and Wei [21] indicated that adaptive control is generally divided into three categories, model reference control, selftuning control and gain schedule control, and presented a review and discussion on the model reference control of parallel manipulator. Wang et al [22] proposed an adaptive back-stepping technique for point control of a planar parallel robot, and experimental results showed that the adaptive back-stepping controller outperforms all the other controllers (mentioned in the paper, i.e., back-stepping controller, adaptive controller, adaptive PD controller, and PD controller) in terms of steady-state errors. Honegger et al [23] proposed a nonlinear adaptive control algorithm and conducted parameters identification of a 6-PSS parallel manipulator employed as a high-speed milling machine.…”
Section: Introductionmentioning
confidence: 99%
“…The stability analysis of the proposed controller has been conducted based on the Lyapunov theory and real-time experiments showed its relevance. In [15], the Backstepping algorithm has been employed to design an adaptive controller for the set-point control of a 2-DOFs planar PKM. Although the aforementioned adaptive controllers may seem quite different, they share one particular limitation.…”
Section: Introductionmentioning
confidence: 99%
“…Though this advanced control strategy has been extensively investigated in serial manipulators [11], [12], it has not gained the same interest in PKMs. In [13], the backstepping technique has been employed to design an adaptive controller for the control of a 2-DOFs planar PKM. The proposed controller was successfully implemented in real-time and showed its superiority in comparison with conventional controllers but it was only developed for set-point trajectories.…”
Section: Introductionmentioning
confidence: 99%